2010
DOI: 10.4103/0970-1591.65396
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and management of urinary retention in women

Abstract: Urinary retention (UR) can be defined as inability to achieve complete bladder emptying by voluntary micturition, and categorized as acute UR, chronic UR or incomplete bladder emptying. UR is common in elderly men but symptomatic UR is unusual in women. The epidemiology of female UR is not well documented. There are numerous causes now recognized in women, broadly categorized as infective, pharmacological, neurological, anatomical, myopathic and functional; labeling symptoms as having a “psychogenic basis” sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Other obstructive causes of urinary retention include; cervical cancer, urethral stenosis, urethral cancer and anti-incontinence surgery [11, 12]. A recent South African review, reporting on 31 women presenting with urinary retention over a 9-year period, identified urethral carcinoma (4/31) and cervical carcinoma (4/31) as the commonest underlying pathology [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other obstructive causes of urinary retention include; cervical cancer, urethral stenosis, urethral cancer and anti-incontinence surgery [11, 12]. A recent South African review, reporting on 31 women presenting with urinary retention over a 9-year period, identified urethral carcinoma (4/31) and cervical carcinoma (4/31) as the commonest underlying pathology [13].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, neurologic conditions (e.g., Fowlers syndrome, spinal cord-compression, and multiple sclerosis) make up the most common causes of acute urinary retention in young to middle-aged women [11, 12]. In a four-year review of cases presenting to their centre, Kavia and colleagues reported Fowlers syndrome (poor relaxation of the external urethral sphincter) as the most common cause of female urinary retention.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of malignant transformation have also been reported [7]. Acute urinary retention in itself is uncommon in women, and bladder or urethral tumors could be considered as one of the possible differential diagnoses [5]. To the best of our knowledge, urinary retention due to a prolapsing IMFT arising from the urinary bladder has never been reported in the literature.…”
Section: Discussionmentioning
confidence: 90%
“…Bladder or urethral tumors can be one of the possible differential diagnoses in such a scenario [5]. We report a patient with IMFT who presented to our emergency department with acute urinary retention due to a prolapsing mass from the urethra.…”
Section: Introductionmentioning
confidence: 99%
“…[1516] Urine analysis appeared as the most useful laboratory test. Although infection of the urinary tract has been reported among underlying factors for urinary retention, its role as a cause or a concurrence in AUR remains uncertain.…”
Section: Discussionmentioning
confidence: 99%